An Educational Mobile Application for Writing Letters, Words, and Punctuation Marks According to PUEBI (General Guidelines for Indonesian Spelling) - Luqman Al-Hakim; Chaulina Alfianti Oktavia (IC-ITECHS, 2022)
Indonesian is a compulsory subject for every student in Indonesia. One of skills that must be possessed in learning Indonesian is writing. In writing, there are various basic rules, to overcome errors in writing, PUEBI is used. In education, technology and information are used as learning media. The game type application can be used as a learning tool with the concept of playing while learning, which is a quiz game model or augmented reality. This research aims to develop an educational mobile application with a theme of writing letters, words, and punctuation marks according to PUEBI. The research method used is research and development methods. The research uses a development model with the Software Development Life Cycle Waterfall method. The application was developed using Unity software and the Vuforia Augmented Reality SDK. In the application, there are 3 menus: Menu Materi, Menu Kuis, and Menu Teks & AR. On the Menu Materi there are learning materials about PUEBI, on the Menu Kuis there are questions and quiz discussions, and on the Menu Teks & AR, there are general knowledge texts, PUEBI discussions, and the augmented reality feature that brings up 3D objects to visualize objects from the text. Based on the results of questionnaire testing from 30 respondents, more than 70% answered "Agree" that the application can improve user understanding of writing Indonesian spelling according to PUEBI.